PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN, KESADARAN MEMBAYAR PAJAK, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (STUDI PADA WAJIB PAJAK KENDARAAN BERMOTOR DI KOTA LANGSA) - Tuti Meutia; Sas Ade Ray; Yani Rizal (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2021)
This study aims to determine the effect of understanding tax regulations, awareness of paying taxes, and tax sanctions on taxpayer compliance (study on motorized vehicle taxpayers in Langsa City). The sampling technique used is simple random sampling technique. The number of samples in this study amounted to 100 respondents. The data analysis method used in this research is multiple linear regression analysis and hypothesis proofing using t test, F test and coefficient of determination analysis. The results of the study obtained multiple linear regression equations, namely: Y= 3.431 + 0.077PPP - 0.152KMP + 0.233SP. The results of the t test show that the understanding of tax regulations has no significant effect on taxpayer compliance with a tsig value of 0.369 > 0.05, awareness of paying taxes does not significantly affect taxpayer compliance with a tsig value of 0.258 > 0.05, and tax sanctions have a significant effect on taxpayer compliance with a tsig value 0.015 < 0.05. From the results of the F test, it is known that understanding of tax regulations, awareness of paying taxes, and tax sanctions simultaneously have no significant effect on motor vehicle taxpayer compliance in Langsa City with Fsig value of 0.072 > 0.10. The results of the analysis of the coefficient of determination show that the contribution of the variable understanding of tax regulations, awareness of paying taxes, and tax sanctions in influencing the compliance of motorized vehicle taxpayers in Langsa City is 0.041 or 4.1% while the remaining 0.959 or 95.9% is influenced by other variables not examined in this study such as service quality, socialization and so on.